KAJIAN ONTOLOGI, EPISTEMOLOGI DAN AKSIOLOGI DALAM PENDIDIKAN ISLAM DI INDONESIA - Tilsep Jasnain Jasnain (STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
ABSTRACT: This paper aims to describe and describe aspects of ontology, epistemology and axiology in Islamic education in Indonesia. In the ontology aspect, Islamic education is generally oriented to form human beings and to integrate the theory of Fitrah. In the epistemological aspect of Islamic education in Indonesia, it examines the development of theory. Discussing things related to knowledge, whether it's